NASKAH SERAT WULANG SUNU SEBUAH SASTRA DIDAKTIS: KAJIAN FILOLOGI - Kamidjan, Kamidjan (Universitas Negeri Surabaya, 2015)
The text of Serat Wulang Sunu, is one of Javanese literary works containing moral teachings. By the researchers the work was classified into the moralistic didactic literature. didactic moralistic. In terms of jkarya content is considered quite good, because the teachings contained in it are universal. Therefore he was copied several times. As evidence in the Sanoguan Museum of Yogyakerta there are two manuscripts, in different manuscripts. Also in Pacitan there is also a script titled the same although the content is longer. The contents contained in it, among others: (1) children and grandchildren and their relatives are obliged to devote to both parents, especially mothers. (keeping the relationship between families in Surakarta palace circle is mandatory.) A kinship is like a pucung, and the relationship between lion and forest is mutually guarded, upholding honesty, avoiding disgraceful deeds associated with ma five, and defying the lust In man is dominated by four kings, the queen of Mutmainah, the queen of Supiah, the King of Anger and the King of Aluamah, who portrayed the human desires, the lust not to be eliminated but controlled, Queen Mutmainah was in charge of the kings.